Greek-Turkish Relations: Crisis in the Aegean - Veremis, Thanos (Études helléniques / Hellenic Studies, 1996)
The Cyprus invasion opened the Pandora’s Box of the Aegean and one after another, the contested issues flew out in periodic succession. The pattern has since become predictable: Every so often a new item is forcefully introduced onto the Greek-Turkish agenda by Turkey. Invitations to bilateral negotiations follow. The January 1996 crisis over the Imia rock constitutes Turkey’s first claim on Greece’s Aegean land territory. Greece’s position that the dispute should be referred to the International Court of Justice was countered by a Turkish proposal that all issues, including the demilitarization of the Greek islands, should be taken to the Hague. The Erbakan government has exposed Turkey to Western criticism, but this situation should not diminish Greek vigilance in the Aegean.